The Materiality of Monarchy of Late Medieval and Early Modern Scotland: An Introduction - Lucy Dean; Amy Hayes (Royal Studies Journal, 2025)
This special issue introduction provides a contextual summary of Scottish kingship and the development of the historiography of royal culture during the reigns of the Stewart/Stuart dynasty, before summarising the articles in the special issue. These summaries are framed and structured by the methodological approaches to material culture evidence embraced by the contributing authors, who include academics, archivists and museum professionals. Despite persistent popular perceptions of Scotland as a cultural backwater in the pre-modern period, the contributions outlined in the introduction demonstrate, even with limited surviving artefacts of cultural heritage for this long-lived dynasty, the depth and complexities of the royal material legacy of Scotland’s pre-modern rulers. In doing so, each contribution enriches our understanding of the ways in which material world was used by and shaped the interactions, whether positive or negative, between monarchs and the populous over which they ruled.